ТЕПЛОТРАНСПОРТНАЯ СПОСОБНОСТЬ ФИТИЛЯ ИЗ МЕТАЛЛИЧЕСКИХ СЕТОК - Горбенко, Геннадий Александрович; Турна, Рустем Юсуфович; Орлов, Роман Сергеевич; Роговой, Евгений Эдуардович (Avìacìjno-kosmìčna tehnìka ì tehnologìâ, 2020)
In the manufacture of wicks for capillary transport of coolant in various heat transfer devices such as heat pipes, capillary pumped loop, accumulators with thermal regulation, evaporative heat exchangers, heat sinks, etc., capillary porous structures are used. Capillary and porous structures made of compressed powders (metal or non-metal) are widely used. However, the technology of making such porous structures is complicated and time-consuming. Important requirements for wicks are high capillary pressure, low-pressure drop, low weight, and manufacturability.  Capillary porous structure, which meets these requirements, can be a wick made of several layers of metal mesh, superimposed on each other, and connected by contact welding. The main advantages of such wicks are low weight and ease of fabrication. The article deals with the methods and results of determining the limit heat transfer capacity of a free wick (not in contact with solid walls) of metal meshes. The design of an experimental unit is given, which allows testing not only at positive but also at small negative angles of the wick to the horizon. Experiments on ammonia to determine the limit heat transport capacity of a flat free wick made of two-layer metal mesh 0.2×0.13 mm woven weave is conducted. By results of the spent experiments dependence of limiting the heat-transport ability of a wick from the temperature of saturation of the heat carrier and an angle of slope to the horizon is received. The performed experiments allow for a wick of the given design to calculate its maximum heat-transport capacity in earth conditions at any width, a transport length of a wick, and an angle of slope to the horizon. Formulas for calculating the thermal transport capacity of wicks made of metal mesh of different length and width under microgravity conditions and in the field of gravity of the earth at different orientations are recommended. The results of the experiments allow determining the thermal transport capacity of wicks from metal meshes and in microgravity conditions.